2005
DOI: 10.1523/jneurosci.4313-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Microdomains Regulate Inositol 1,4,5-Trisphosphate-Mediated Intracellular Calcium Transients in Cultured Neurons

Abstract: Ca2ϩ signals in neurons use specific temporal and spatial patterns to encode unambiguous information about crucial cellular functions. To understand the molecular basis for initiation and propagation of inositol 1,4,5-trisphosphate (InsP 3 )-mediated intracellular Ca 2ϩ signals, we correlated the subcellular distribution of components of the InsP 3 pathway with measurements of agonist-induced intracellular Ca 2ϩ transients in cultured rat hippocampal neurons and pheochromocytoma cells. We found specialized dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 44 publications
(61 reference statements)
3
45
0
1
Order By: Relevance
“…It has been shown in previous studies that CGB and PIPK Iγ could be found co-located closely within neuronal cells (Jacob et al, 2005). Preventing the kinase from phosphorylating InsP 3 precursors by applying Wortmannin and blocking CGB binding to the InsP 3 R1 had similar effects on the Ca 2+ release pattern (Choe et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…It has been shown in previous studies that CGB and PIPK Iγ could be found co-located closely within neuronal cells (Jacob et al, 2005). Preventing the kinase from phosphorylating InsP 3 precursors by applying Wortmannin and blocking CGB binding to the InsP 3 R1 had similar effects on the Ca 2+ release pattern (Choe et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies showed similar distribution patterns for InsP 3 R1 mRNA (Furuichi et al, 1993) and protein distribution (Fotuhi et al, 1993) in rat and human hippocampal tissue. Furthermore, the low-threshold InsP 3 R1 has been shown to be localized throughout the cell in neuron-like PC12 cells (Johenning et al, 2002) and hippocampal pyramidal neurons (Seymour-Laurent and Barish, 1995;Jacob et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream effects of activating CaV1.3 channels include increased IP 3 -sensitive internal store release via a CaV1.3-ShankHomer interaction, potentially creating a signaling microdomain (Jacob et al, 2005) that leads to increased levels of the transcription factor pCREB (supplemental Fig. 1, available at www.…”
Section: Discussionmentioning
confidence: 99%
“…CGB resides in the sarcoplasmic reticulum (SR) and functionally interacts with the InsP 3 R to shape Ca 2+ release. [9][10][11][12] Therefore, co-existence of CGB and the InsP 3 R in cardiomyocytes suggests a functional role for CGB in shaping cardiomyocyte InsP 3 -dependent Ca 2+ signaling.…”
Section: Cardiomyocytes Express Cgb Along With All Insp 3 R Isoformsmentioning
confidence: 97%
“…[10][11][12] Local InsP 3 -dependent Ca 2+ signaling was only recently linked to cardiac excitation-transcription coupling (ETC) in adult ventricular myocytes. 13 Because we found that neonatal and adult ventricular cardiomyocytes express CGB along with all three isoforms of the InsP 3 R, we hypothesized that CGB would be important in the regulation of cardiomyocyte InsP 3 -dependent Ca 2+ signaling and would modify ETC.…”
Section: Introductionmentioning
confidence: 99%